P131 Are green jobs safe jobs? identifying research gaps on chemical and biological hazards. (1st September 2016) - Gravel, Sabrina; Labrèche, France; Zayed, Joseph
Abstract : The transition to a greener economy is based on new technologies, innovative and modified processes, or new materials with less severe environmental impact. However, little is known on the occupational hazards associated with these new green jobs. The objective of this study is to identify the major occupational health and safety (OHS) issues and research gaps regarding chemical and biological hazards in green jobs. Literature reviews and progress reports of OHS research institutes were analysed to assess the current state of knowledge. Expert forecasts, research recommendations, stakeholders' surveys, and white papers allowed identification of research needs. Finally, a portrait of the ongoing or recent research was based on all projects listed by 20 targeted international OHS research institutes. This search covered documents published between 2008 and 2014. Four major industrial sectors stand out as high-priority for research on green jobs, in terms of the associated hazards and of the number of exposed workers: energy supply (solar, wind, biofuel and transport electrification), waste treatment (sorting, recycling, composting, biogas harvesting), construction, and green chemistry. The key issue is either new occupational hazards, or known hazards encountered in new work conditions. Noteworthy are the use of toxic metals in fabrication of solar panels and batteries, and the production of potentially harmful bioaerosols during waste treatment. Ten research institutions, in Europe, US, and Canada were found to conduct or fund projects on chemical and biological hazards related to these industries. They focus on exposure characterisation and risk assessment, with only two epidemiological studies investigating the health effects of biofuel dust and those associated with biological agents in composting plants. Although recent OHS research efforts have been devoted to green jobs, this is still an underdeveloped niche and research needs are still numerous in terms of hazard identification and exposure and risk assessments.